Lingual nerve injuries during oral surgery procedures: views and perpectives - Salgado, Abel (2020)
Lingual nerve being one of the most important nerves within the oral cavity, it is very often injured during some oral surgery procedures. The clinical presentation of lingual nerve injury, its epidemiology, predisposing factors, and anatomy are explored to identify those patients at risk for developing neuropathic pain. Due to its importance when it comes to guarantee the correct oral surgery procedures, this work aims to identify any factors that could aid the surgeon in preventing or minimizing the risk of lingual nerve injury during some oral surgery. Nevertheless, results should be interpreted with extreme caution because of the considerable heterogeneity of the data and the considerable influence of several anatomic and surgical variables that were closely related, but difficult to analyze independently.